Fikih Kebangsaan: Methodology and Foundations for Unity, Tolerance, and National Defense - Muhammad Arfan Ahwadzy; Muhammad Daffa Syafiq Nashr ad-Diba’i; Aiman Hakim (The Institute of Research and Service Community IPMAFA Pati, 2026)
The development of fiqh in Indonesia reflects post-reform socio-political dynamics and the need to situate Islamic law within a pluralistic nation-state. Existing studies, however, tend to emphasize cultural and normative harmonization without offering a robust theoretical framework grounded in clear epistemological assumptions. This methodological gap shows the difficulty of integrating the classical Islamic intellectual tradition (turāth) with contemporary national demands. This article argues for a conceptual framework of Fikih Kebangsaan (National Fiqh) to bridge turāth with the Indonesian context. Using a qualitative library research approach and conceptual analysis, the study finds that Fikih Kebangsaan rests on three pillars: state-based unity, interreligious tolerance, and the reinterpretation of jihad in the context of national defense. These findings demonstrate the epistemological flexibility of turāth in addressing modern nationhood. This study proposes an initial methodological framework for Fikih Kebangsaan as a normative and operational basis for developing contextual fiqh in Indonesia.